Would you add some kWhs to your food order? A forward-looking perspective on the energy landscape disruption portrayed by future actors in a distributed system. (December 2022) - Shaviv, Elad; Parag, Yael; Teschner, Naama; Zemah-Shamir, Shiri
Abstract: Distributed energy systems (DES), made possible by decentralized energy generation and management, are growing in number and present opportunities for cheaper, cleaner, and prevalent energy supplies to local energy consumers and communities. The emergence of these systems reshuffles the traditional hierarchical, well-defined electric power structure to a flatter, multi-actor, modular market. This transition brings new actors and innovative business models, blurring the boundaries between energy producers and consumers. Such changes may call for adaptation of energy policies and governance procedures, currently prioritizing incumbent actors. This study explores and highlights the possible need for a novel approach to define DES actors and their roles to ensure effective governance by the different stakeholders. The findings of this study are based on forward-looking perspectives from academic experts and industry practitioners, indicating a diminishing influence by the incumbent actors in the future DES market, alongside mixed and diversified roles by a future actor. Furthermore, the analysis indicates a sound expectation that non-energy actors will diversify their business to play a role in a disrupted future DES market. The characteristics, roles, and motivations of such future actors will differ from current actors in the energy market. This also requires careful attention to ensure the adequacy of the models and theories governing the power system in such a new market. Based on the innovative disruption theory, we take the first stance to propose a new actor classification and mapping concept that can capture the ongoing market and actor dynamics.